Estimation and monitoring of grass nitrogen and phosphorus using Sentinel-2 derived spectral information and vegetation indices in a Savanna ecosystem - Ramoelo, Abel (University of Pretoria, 2023)
Dissertation (MSc (Geography))--University of Pretoria, 2023.